Medicinal plants with neuroprotective potential in East African countries: A systematic review - Ibe Michael Usman; Ekom Monday Etukudo; Elna Owembabazi; Wusa Makena; Augustine Oviosun; Makeri Danladi; Vivian Ojiakor; Patrick Maduabuchi Aja; Emeka Anyanwu; Yanurkis Duranones Rosales; Mario Edgar Fernandez Diaz; Josiah Ifie; et al. (Phytomedicine Plus, 2025)
Background: The use of plant-derived natural compounds in the management of various human disease conditions has gained lots of attention in recent times; hence, the present study examined medicinal plants with neuroprotective potential in East Africa and their mechanism of action. Method: The present study is a systematic review that included randomized controlled trial studies using experimental animal models for various nervous system related conditions treated with medicine plants sourced from within any of the East African countries. Result: Most of the included studies were conducted in Kenya 6/12 (50 %). Studies from Ethiopia and Uganda accounted for 2/12 (16.7%) and 4/12 (33.3 %) respectively. One-third of the included studies used the leaves of the selected plants. The reviewed studies highlighted neuroprotective activities of the plants, as evidenced by biochemical and behavioral improvements. Key findings included increased levels of glutamine synthetase, Na+/K+ ATPase, calcium ATPase, acetylcholinesterase, catalase, and superoxide dismutase, all of which support enhanced neuronal function and protection against oxidative stress. Conversely, there was a significant decrease in level of malondialdehyde, an important marker of lipid peroxidation, indicating reduced cellular damage from oxidative stress. Behavioral outcomes aligned with these biochemical changes, showing marked improvements in memory and learning, motor activity, seizure threshold, and anxiety-like behavior. Conclusion: The included studies collectively suggest a strong neuroprotective activity, with the biochemical enhancements contributing to better neurological health and functional recovery. Hence, the reported plants could be explored as options in complementary and alternative medicine following a thorough examination of their active ingredient and mechanism of action.